PENGARUH PENGELOLAAN INFORMASI DAN KEWIRAUSAHAAN TERHADAP KEMAMPUAN INOVASI PRODUK PADA INDUSTRI KECIL DAN MENENGAH (IKM) BATIK KAYU KREBET KABUPATEN BANTUL - Laurenti Delani Winarno; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2018)
Product innovation capability of the small and medium industry can be affected by a variety of factors, both internal and external company factors. The purpose of this research is to know the influence of the information management and entrepreneurship against the industries performance of small and medium enterprises. The research type is explanatory research. This study uses sensus method which all of the population becomes respondent. Data collecting using a questionnaire and interviews. Data analysis using simple and doubled linier regression analysis using IBM SPSS 20.Results of statistical analysis known that together the information management and entrepreneurship effect on product innovation capabillty.The conclusion from this study is that there is a positive and significant influence between information management and entrepreneurship to product innovation capability on the Small and Medium Industry of Wooden Batik Krebet Bantul. Researcher suggest that IKM improve all of the informations that related to business so can always support the continuance of business, and improve the capabillty to build any idea for create products that can be accept by market.